Analysis of the main dosimetric peak of Al2O3:C compounds with a model of interacting traps - Ortega, Federico Martin (2013)
The glow curve of Al2O3:C compounds has been analyzed by employing a model consisting of two active traps, thermally disconnected traps and one recombination centre. The analysis takes into account interaction among traps and the thermal quenching of the thermoluminescent emission.